PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 - 2016 - Mukti Bagus Susilo; Fuad Fuad (Diponegoro Journal of Accounting, 2018)
This study aims to provide empirical evidence about the relationship between Good Corporate Governance which is proxied by Independent Board of Directors, Audit Committee, Ownership Managerials, Ownership Institutions towards profitability which is measured by Return on Assets.The objects of this study are manufacture companies on Indonesia Stock Exchange. The sampling method of this study is purposive sampling that based on criterion which has been determined before. Hypotheses in this study are tested by descriptive statistic and data panel regression analysis method.The results of statistical test (F test) shows that Good Corporate Governance which is proxied by Independent Board of Directors, Audit Committee, Ownership Managerials, Ownership Institutions affects Return On Asset. The effect of independent variable Good Corporate Governance towards Return on Assets on the t test is significant.